Silent diabetes mellitus, periodontitis and a new case of thalamic abscess. (21st July 2014) - Karageorgiou, Ioannis; Chandler, Christopher; Whyte, Martin Brunel
Abstract : Brain abscess is an unusual complication of uncontrolled diabetes. A solitary thalamic abscess is an uncommon type of brain abscess. We report a case of thalamic abscess, whereupon diabetes mellitus and periodontitis were diagnosed. The diagnosis and management of thalamic abscess, and the interplay of type 2 diabetes and periodontitis are discussed. A 56-year-old, Caucasian, man with no medical or travel history, presented with 5-day symptoms of meningeal irritation. Body mass index 30.6 kg/m 2 . CT demonstrated a solitary midline lesion with neoplasia as a differential diagnosis. It was biopsied and cultures grew Streptococcus milleri . He was treated by stereotactic puncture, external drainage and targeted intrathecal and systemic antibiotic therapy. HIV negative but glycated haemoglobin (HbA1c) 10.7% (93 mmol/mol). Dental examination revealed a small molar abscess. Radiological resolution of the thalamic abscess occurred within 2 months. Diabetes improved with 7 weeks of insulin, and maintained on metformin, HbA1c 6.9% (51 mmol/mol). There was no residual neurological disability.